Adaptive strategies of Burkholderia cenocepacia to long term residence in the lungs of cystic fibrosis patients - Maldonado, Cláudia Rita Ferreira, 1990- (2013)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2012 [Versão pública]